Answer:
[tex]\displaystyle a = \frac{-11}{3}[/tex]
General Formulas and Concepts:
Pre-Algebra
Order of Operations: BPEMDAS
- Brackets
- Parenthesis
- Exponents
- Multiplication
- Division
- Addition
- Subtraction
Equality Properties
- Multiplication Property of Equality
- Division Property of Equality
- Addition Property of Equality
- Subtraction Property of Equality
Algebra I
- Exponential Rule [Powering]: [tex]\displaystyle (b^m)^n = b^{m \cdot n}[/tex]
- Exponential Rule [Rewrite]: [tex]\displaystyle b^{-m} = \frac{1}{b^m}[/tex]
Step-by-step explanation:
Step 1: Define
Identify
[tex]\displaystyle 9 = (\frac{1}{27})^{a + 3}[/tex]
Step 2: Solve for a
- Rewrite: [tex]\displaystyle 3^2 = (\frac{1}{27})^{a + 3}[/tex]
- Rewrite: [tex]\displaystyle 3^2 = (\frac{1}{3^3})^{a + 3}[/tex]
- Rewrite [Exponential Rule - Rewrite]: [tex]\displaystyle 3^2 = (3^{-3})^{a + 3}[/tex]
- Exponential Rule [Powering]: [tex]\displaystyle 3^2 = 3^{-3(a + 3)}[/tex]
- Set up: [tex]\displaystyle 2 = -3(a + 3)[/tex]
- [Division Property of Equality] Divide -3 on both sides: [tex]\displaystyle \frac{-2}{3} = a + 3[/tex]
- [Subtraction Property of Equality] Subtract 3 on both sides: [tex]\displaystyle \frac{-11}{3} = a[/tex]
- Rewrite: [tex]\displaystyle a = \frac{-11}{3}[/tex]